Combinations of Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. Extracts with Selected Antibiotics Against Antibiotic-Resistant Bacteria: Bioactivity and Phytochemistry - Gagan Tiwana; Ian Edwin Cock; Matthew James Cheesman (MDPI AG, 2024)
Antimicrobial resistance (AMR) has arisen due to antibiotic overuse and misuse. Antibiotic resistance renders standard treatments less effective, making it difficult to control some infections, thereby increasing morbidity and mortality. Medicinal plants are attracting increased interest as antibiotics lose efficacy. This study evaluates the antibacterial activity of solvent extracts prepared using Terminalia bellirica and Terminalia chebula fruit against six bacterial pathogens using disc diffusion and broth microdilution assays. The aqueous and methanol extracts of T. bellirica and T. chebula showed substantial zones of inhibition (ZOIs) against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). The activity against those bacteria was strong, with minimum inhibitory concentrations (MIC) ranging from 94 µg/mL to 392 µg/mL. Additionally, the T. bellirica methanolic extract showed noteworthy antibacterial activity against Escherichia coli and an extended spectrum β-lactamase (ESBL) E. coli strain (MIC values of 755 µg/mL for both). The aqueous T. bellirica and T. chebula extracts also inhibited Klebsiella pneumoniae growth (MIC values of 784 µg/mL and 556 µg/mL, respectively). The corresponding methanolic extracts also inhibited ESBL K. pneumoniae growth (MIC values of 755 µg/mL and 1509 µg/mL, respectively). Eighteen additive interactions were observed when extracts were combined with reference antibiotics. Strong antagonism occurred when any of the extracts were mixed with polymyxin B. Liquid chromatography-mass spectroscopy (LC-MS) analysis of the extracts revealed several interesting flavonoids and tannins, including 6-galloylglucose, 1,2,6-trigalloyl-β-D-glucopyranose, 6-O-[(2E)-3-phenyl-2-propenoyl]-1-O-(3,4,5-trihydroxybenzoyl)-β-D-glucopyranose, propyl gallate, methyl gallate, sanguiin H4, hamamelitannin, pyrogallol, gallic acid, ellagic acid, chebulic acid, and chebuloside II. All extracts were nontoxic in brine shrimp assays. This lack of toxicity, combined with their antibacterial activities, suggests that these plant species may be promising sources of antibacterial compound(s) that warrant further study.